The relationship between the use of metformin and the risk of pancreatic cancer in patients with diabetes: a systematic review and meta-analysis - Jian Hu; Hong-Dan Fan; Jian-Ping Gong; Qing-Song Mao (BMC Gastroenterology, 2023)
Abstract Objective We aim to evaluate the relationship between the use of metformin and the risk of pancreatic cancer in type 2 diabetes patients. Method We systematically searched the observational studies on PubMed, Embase, Web of Science, Cochrane Library, clinicalrials.gov, and CNKI databases, extracted relevant data, combined the OR value and 95% CI using the random effect model, and conducted a sensitivity analysis, subgroup analysis, and meta-regression to evaluate the size and stability of this relationship. Result Twenty-nine studies from twenty-four articles met our inclusion criteria, including more than 2 million subjects. Overall analysis showed that compared with no use of metformin, the use of metformin could reduce the risk of pancreatic cancer in patients with type 2 diabetes (OR = 0.82, 95% CI (0.69, 0.98)). Subgroup analysis showed that compared with the use of hypoglycemic drugs, the use of metformin could reduce the risk of pancreatic cancer in patients with type 2 diabetes (OR = 0.79, 95% CI (0.66, 0.94)). However, compared with no drugs or only diet therapy, metformin users might increase the risk of pancreatic cancer (OR = 2.19, 95% CI (1.08, 4.44)). Sensitivity analysis confirmed the stability of the study, and there was no significant publication bias. Conclusion Compared with the no-use of metformin, metformin users with diabetes can reduce the risk of pancreatic cancer. More research is needed to prove it works.